Frequently Transmission and Close Relationship Among Immigrants in the China–Myanmar Border Region Indicated by Molecular Transmission Analysis From a Cross-Sectional Data - Hu, Zhili; Liu, Yingjie; Wang, Jibao; Meng, Zhefeng; Leuba, Sequoia I.; Wei, Jie; Duan, Xing; Chu, Zhenxing; Chen, Min; Shang, Hong; Xu, Junjie (Frontiers in Medicine, 2022)
Background Accurate identification of molecular transmission clusters (MTCs) and understanding the dynamics of human immunodeficiency virus (HIV) transmission are necessary to develop targeted interventions to prevent HIV transmission. We evaluated the characteristics of antiretroviral therapy-naïve individuals who belonged to HIV-1 MTCs in the China–Myanmar border region to inform targeted effective HIV intervention. Methods Phylogenetic analyses were undertaken on HIV-1 pol sequences to characterize subtypes or circulating recombinant forms and identify MTCs. MTCs were defined as those with 2 or more sequences having bootstrap support > 80% and a pairwise gene distance less than or equal to 0.03. Factors correlated with MTCs were evaluated using logistic regression analysis. The chi-square test was used to compare differences between Chinese and Burmese participants belonging to MTCs. Results A total of 900 people had their pol gene successfully sequenced. Twenty-one MTCs were identified and included 110 individuals (12.2%). Individuals in MTCs were more likely to be Burmese [aOR = 2.24 (95% CI: 1.33, 3.79), P = 0.003], be younger [aOR = 0.34 (95% CI: 0.20, 0.58), P < 0.001 for age 26–50 vs. 25 years or younger], have a lower CD4 T cell count [aOR = 2.86 (95% CI: 1.34, 6.11), P = 0.007 for < 200 vs. 350 or greater], and have subtypes CRF07_BC or C [CRF07_BC: aOR = 7.88 (95% CI: 3.55, 17.52), P < 0.001; C: aOR = 2.38 (95% CI: 1.23, 4.62), P = 0.010 compared to CRF01_AE]. In MTCs, Burmese were younger (89.7 vs. 57.7% for age 25 years or younger), had a lower education level (41.0 vs. 8.5% for illiterate), were more likely to be infected through injection drug use (35.9 vs. 12.7%), and had a higher proportion of subtype BC (33.3 vs. 15.5%) and CRF01_AE (20.5 vs. 8.5%) compared to Chinese (P < 0.05 for all). Conclusion Burmese participants were more likely to belong to MTCs, and most MTCs had both Burmese and Chinese participants. These data highlight the bidirectional transmission of HIV-1 frequently transmission and close relationship among immigrants in the China–Myanmar border region. Local health departments should pay more attention to HIV screening and intervention to immigrants Burmese with the characteristics of younger age, having lower CD4 T cell count and infected with HIV subtypes CRF07_ BC or C.